A HIERARCHICAL TOPSIS METHOD BASED ON TYPE-2 FUZZY SETS TO EVALUATE SERVICE QUALITY OF PUBLIC TRANSPORTATION - dehghani, ali (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
In this paper, a novel fuzzy Multiple Attribute Decision Making model is proposed for evaluate service quality of public transportation. Evaluation of service quality of public transportation systems is vital to improve productivity, gain profits and increase customer satisfaction,so, a systematic and scientific approach is necessary for its solution. In this study, a Hierarchical TOPSIS method based on interval type-2 fuzzy is proposed in which a group of experts determine the values and the weights of attribute and for calculating and comparing the alternatives, operators, and efficient functions on type-2 fuzzy sets are used. The steps of the method are described first, and then an application of the proposed method for evaluation of service quality of Public Transportation in Shahrekord is provided.